The Environmental Effect of Land Use in the Tenure Systems in Ghana - Libor Grega (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
This paper examines the land tenure system in Ghana and its impact on the environment. The main forms of land tenure systems are explained and the positive and negative impacts of each of these forms on the environment analysed. Specific attention is devoted to deforestation and soil depletion. The complex problems of land acquisition in Ghana, and the inherent insecurity effects on farming, which is considered to be the most important economic activity in the rural areas are examined. The analyses and the result proved that the insecurity of land tenure system has a direct relationship with the environment. Cross-sectional data analyses establishes that traditional forms of land acquisitions, ownership and land use form part of the main causes of environmental degradation in Ghana.